Relations between Temperament and Metacognition and Frames of Reference in Behaviors in Public Situations in Early and Middle Adolescence: An Analysis of Age Stages - Kanzaki, Nana; Kubota, Kenichi; Nakagawa, Atsuko (Frontiers in Education, 2018)
We conducted a questionnaire survey using a cross-sectional sample of early and middle adolescents aged 10 to 15 (N = 351) in order to investigate relationships between temperament, metacognition, and frames of reference in behaviors in public situations. The sample was divided into two groups by age (Early-adolescence group:10–12; Middle-adolescence group:13–15) and were analyzed by Multiple Group Structural Equation Modeling. Explanatory variables were four components of temperament (Effortful Control, Affiliativeness, Surgency, and Negative Affect) and Metacognition. Objective variables were three components of frames of reference in behaviors in public situations (Egocentrism, Neighborhood Evaluation, and Public Values). In both age groups, Effortful Control had a negative effect on Egocentrism, and Surgency had a negative effect on Neighborhood Evaluation. However, only in the middle-adolescence group did Affiliativeness and Negative Affect have significant effects on Public Values. Meanwhile, metacognition in the early-adolescence group had a positive effect on Egocentrism and Neighborhood Evaluation, but these relations disappeared in the middle-adolescence group, and only in the middle-adolescence group did Metacognition have a positive effect on Public Values. We discuss frames of reference in behaviors in public situations from the viewpoint of the development of social cognition in early and middle adolescence in relation to temperament and metacognition.